RENEWABLE ENERGY RESOURCES AND NON-CONVENTIONAL ENERGY SOURCES - Ikromova Mashhura Asqar qizi (American Journals, 2024)
In this article, information is provided about renewable energy sources, the utilization of solar energy, hydroelectric power sources, wind power plants, and energy derived from seas and oceans. This paper provides a comprehensive overview of innovative approaches for the effective deployment of renewable energy technologies.
Keywords: Solar radiation, hydroelectric power, wind energy, wave energy, non-conventional energy.